A case report of a brain herniation secondary to cryptococcal meningitis with elevated intracranial pressure in a patient with Human Immunodeficiency Virus/Acquired immunodeficiency syndrome (HIV/AIDS). (2022) - Guevara, Nehemias; Akande, Abdulrasheed; Chang, Mailing Flores; Atallah, Jane; Epstein, Carol
Abstract: Background: Cryptococcal meningitis is a major opportunistic infection in individuals with HIV. The worldwide annual incidence is estimated to be approximately one million cases per year, with the most significant burden in sub-Saharan Africa. HIV-associated cryptococcal meningitis continues to have a high mortality rate despite widespread availability and use of HAART. Case: 36-year-old male with a past medical history of AIDS and a CD4 count of 35 cells/mm3 presented with altered mental status initially thought to be related to using crystalline methamphetamine as reported by EMS. However, a lumbar puncture performed in the emergency department showed elevated CSF opening pressure of 29 cmH2O and positive CSF and serum cryptococcal antigen. The patient was admitted and commenced treatment according to the current IDSA guideline but continued to have waxing and waning mental status. On the fourth day of admission, he complained of headache, had a witnessed seizure, and was taken emergently for a CT scan of the brain, which was negative for any acute intracranial process, but suffered a cardiac arrest before it could be done. He was intubated and transferred to the intensive care unit. CT brain follow-up showed anoxic encephalopathy, development of marked cerebral edema, and complete effacement of the basilar cisterns, suggestive of downward transtentorial herniation; he continued to deteriorate and expired on the seventh day of admission. Objectives: 1. Describe a case of brain death secondary to increased intracranial pressure due to cryptococcal meningitis in a patient with HIV/AIDS. 2. Explain the mechanisms of elevation in intracranial pressure in patients with cryptococcal meningitis. 3. Discuss the options for managing elevated intracranial pressure in patients with cryptococcal meningitis. 4. Create awareness in the medical community about the importance of prompt and efficient management of increased intracranial pressure in patients with cryptococcal meningitis. Conclusion: This case highlights the importance of aggressive management of elevated intracranial pressure in cryptococcal meningitis. It reiterates the need for more data regarding the optimal timing and frequency of therapeutic lumbar puncture and the use of temporary lumbar drainage catheters and ventriculostomy to manage this potentially fatal complication.